Creating a sperm bank from sturgeon brood stocks in the South Caspian Sea - Baradaran Noveiri, Shahrouz; Alipoor, A.R.; Mohseni, M.; Pordehghani, M.; Chakmedooz, F.; Halajiyan, A. (Iranian Fisheries Science Research Institute, 2012)
Sturgeon stocks are drastically decreasing in Caspian Sea during recent decades. This project has been proposed to collect the excess sperm of Caspian Sea Southern part sturgeon breeders, to cryopreserve and hold them for further use. During two spawning seasons (2006-2007), sperm quality and quantity analysis were conducted on 34 different male sturgeons of which 12 Persian sturgeon, 4 stellate sturgeon, 1 beluga and 1 ship sturgeon with better quality were chosen to cryopreserve. After dilution of fresh sperm with sturgeon sperm diluent (115 mM Tris, 23.4 mM sucrose and 15% DMSO) at the ratio of 1:1, the 0.5 ml straws were filled using special filling and sealing apparatus and frozen with a multi step freezing rate. To access the further quality and fertilization test, samples were thawed at 40 °C for 20 seconds. During the project performance, 1010 ml of Persian sturgeon sperm , 110 ml of ship sturgeon sperm , 90 ml of stellate and 80 ml of beluga sperm were cryopreserved. The reduction of frozen-thawed sperm motility in comparison with fresh samples showed 10-52.3 % decrease, but there was not any significant differences between samples after 7 months preservation in liquid Nitrogen (P < 0.005). River caught Persian sturgeon samples showed higher sperm density in comparison with nonriverine breeders (P < 0.05). Data showed that stellate sturgeon sperm showed better resistance to freezing condition in comparison with Persian sturgeon spermatozoa. Fertilization tests (4 hours after fertilization)showed 27.4% and 58.2% fertilization rate in frozen-thawed stellate and Persian sturgeon spermatozoa, respectively. Iranian Fisheries Science Research Institute Published